USP37 prevents unscheduled replisome unloading through MCM complex deubiquitination - Derek L. Bolhuis; Dalia Fleifel; Thomas Bonacci; Xianxi Wang; Brandon L. Mouery; Jeanette Gowen Cook; Nicholas G. Brown; Michael J. Emanuele (Nature Communications)
Abstract The CMG helicase (CDC45-MCM2-7-GINS) unwinds DNA as a component of eukaryotic replisomes. Replisome (dis)assembly is tightly coordinated with cell cycle progression to ensure genome stability. However, factors that prevent premature CMG unloading and replisome disassembly are poorly described. Since disassembly is catalyzed by ubiquitination, deubiquitinases (DUBs) represent attractive candidates for safeguarding against untimely and deleterious CMG unloading. We combined a targeted loss-of-function screen with quantitative, single-cell analysis to identify human USP37 as a key DUB preventing replisome disassembly. We demonstrate that USP37 maintains active replisomes on S phase chromatin and promotes normal cell cycle progression. Proteomics and biochemical assays revealed USP37 interacts with the CMG complex to deubiquitinate MCM7, antagonizing replisome disassembly. Significantly, USP37 protects normal epithelial cells from oncoprotein-induced replication stress. Our findings reveal USP37 to be critical to the maintenance of replisomes in S phase and suggest USP37-targeting as a potential strategy for treating malignancies with defective DNA replication control.